1987
DOI: 10.1128/aem.53.9.2082-2089.1987
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal activities of selected organic N-halamines

Abstract: The bactericidal efficacies of three organic N,N'-dihalamine disinfectants in the class of compounds termed imidazolidinones were determined for combinations of pH, temperature, and water quality treatments by using Staphylococcus aureus and Shigella boydii as test organisms. The compound 1,3-dibromo-4,4,5,5-tetramethyl-2-imidazolidinone was found to be the most rapidly acting bactericide, especially under halogen-demand-free conditions. The mixed N,N'-dihalamine 1-bromo-3-chloro-4,4,5,5-tetramethyl-2-imidazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Chlorinated compounds have been used for disinfection purposes since the early 1900s due to their effective bactericidal action 1. They can act either as free small species, such as HOCl or NaOCl (which are considered to be the most effective disinfectants for water and clinical purposes),2–5 attached to amino containing compounds ( N ‐halamines), such as halogenated isoxazoles and halogenated imidazoles,6–11 or attached to high molecular weight compounds ( N ‐halamine polymers) 12–16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorinated compounds have been used for disinfection purposes since the early 1900s due to their effective bactericidal action 1. They can act either as free small species, such as HOCl or NaOCl (which are considered to be the most effective disinfectants for water and clinical purposes),2–5 attached to amino containing compounds ( N ‐halamines), such as halogenated isoxazoles and halogenated imidazoles,6–11 or attached to high molecular weight compounds ( N ‐halamine polymers) 12–16…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the action of halogenated heterocyclic compounds ( N ‐halamines) depends on halogen ion exchange between these compounds and the bacterial cell membrane by contact, resulting in cellwall oxidation 6–11. The same explanation has been suggested for the mode of action of N ‐halamine biocidal polymers, but it is still not clear whether the halogen ion is delivered to the bacterial cells by contact,12, 13 halogen ion release22 or a combination of both 16.…”
Section: Introductionmentioning
confidence: 99%
“…Disinfectant (10 ppm of total chlorine [final concentration]) was added to the cell suspension 5 to 10 min before the acid pulse. It should be noted that the ratio of cells to disinfectant was approximately 100 to 500 times that ratio used when disinfection kinetics experiments were performed (22)(23)(24).…”
Section: Methodsmentioning
confidence: 99%
“…Most of the work conducted has involved the assessment of biocidal activity of the compounds rather than investigations of the possible mode of action of these compounds. It has been shown that the halamine disinfectants discussed have a wide range of biocidal activities based on the compound, pH, water quality (high halogen demand versus demand free), temperature, and test organism (15,19,(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…In this regard, antimicrobial agents including Ag nanoparticles, polybiguanides, chitosan, quaternary ammonium salts (QAs), and N ‐chloramines have been thus successfully incorporated into cotton fabrics. Among these biocides, both QAs and N ‐chloramines have been widely used either in aqueous or by immobilization on substrate surface . However, QAs are usually regarded as incompatible with anion surfactant, and bacterial resistances to QAs have been reported, which may greatly restrict its applications.…”
Section: Introductionmentioning
confidence: 99%